(untitled) (International Seven Journal of Multidisciplinary, 2025)
Brazil is facing rapid population growth, resulting in no increase in the incidence of Alzheimer’s disease (AD), a neurodegenerative condition that compromises memory, motor coordination and functionality. DA is classified in three stages: mild, moderate and advanced, with progressive aggravation of two symptoms.Initially, it is manifested by subtle memory deficits and discrete motor alterations. In the moderate phase, these dysfunctions become more evident, affecting daily activities. If this is not advanced, cognitive and motor impairments become severe, requiring continued assistance due to loss of autonomy. Embora incurável, physiotherapy plays an essential role in the maintenance of mobility, strength and balance, contributing to slowing down the progress of the disease and preventing complications, promoting greater independence.